Near-field analysis of E-plane sectoral solid dielectric horn antennas - Singh A.K.; Jha B.; Jha R.K. (My University, 2025)
An approximate analysis of the aperture field of an E-plane sectoral solid dielectric horn antenna is described using the TE to x mode. The analysis is based on the solution of Maxwell's equations after making some simplifying assumptions. The electric and magnetic fields inside the horn core are matched to those outside at appropriate boundaries to yield transcendental equations which are then solved on a computer for the ropagation constants and field configurations. The theoretical results so obtained are in agreement with experimental results. Characteristic equations for the TM to x mode are also calculated and the results are compared with those of Marcatili, Goell, Eyges and Morita. © 1991 Taylor & Francis, Ltd.